Gone is gone : wildlife under threat - Groc, Isabelle (Orca wild., 2019)
"This nonfiction book for middle readers looks at why and what species have become endangered, how scientists are learning about endangered wildlife, what people are doing to conserve species and what young people can do to help. Illustrated with unique photos by the photo-journalist author. "--